Limitation of photosynthetic activity by CO2 availability in the chloroplasts of oak leaves from different species and during drought - Roupsard, O.; Gross, P.; Dreyer, E. (Ann. For. Sci., 1996)
It has recently been suggested that the low photosynthesis rates in tree species as compared to highly productive crops is at least partly due to resistances opposing the CO 2 fluxes in the mesophyll of tree leaves. To validate this assertion, values of CO2 mole fractions in the chloroplasts of leaves from Quercus petraea, Q robur, Q ilex and Populus sp were estimated on the basis of the analysis of the partitioning of light driven electron flow between fractions used for the carboxylation or the oxygenation of RuBP by Rubisco. The procedure used included: i) a measure of total light driven electron flows derived from the chlorophyll a fluorescence ratio ΔF/Fm', which is proportional to the photochemical efficiency of PS II, multiplied by incident irradiance and a calibration coefficient; ii) an estimation of the electron flux devoted to carboxylation obtained from net CO2 assimilation and respiration rate measurement, and using the known electron requirements (four electrons for CO2 or O2 fixation); iii) the derivation of the CO2 mole fraction in the chloroplasts from the specificity factor of Rubisco, and the ratio of carboxylation/oxygenation of RuBP. Results showed that in the absence of drought stress, the mole fraction of CO2 in the chloroplasts (35-45% of the atmospheric one) was much lower than the calculated substomatal one (60-70% of the atmospheric) in all species. Moreover, lowest values were recorded in the species with lowest assimilation rates, suggesting that the differences in the net CO 2 assimilation rate between species are linked to the CO2 availability in the chloroplasts. Finally, the CO2 availability decreased with increasing drought in the soil, stressing the importance of reduced influx of CO2 as an important factor for drought-induced declines of photosynthesis. These results are discussed with respect to the occurrence of significant resistances in the leaf mesophyll, in addition to the stomatal resistances.
Keywords: chlorophyll fluorescence; chloroplasts; CO2 diffusion; Drought; mesophyll conductance; oaks; Stomatal conductance